2014
DOI: 10.1103/physrevd.89.084040
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational collapse of Bose-Einstein condensate dark matter halos

Abstract: We study the mechanisms of the gravitational collapse of the Bose-Einstein condensate dark matter halos, described by the zero temperature time-dependent nonlinear Schrödinger equation (the Gross-Pitaevskii equation), with repulsive inter-particle interactions. By using a variational approach, and by choosing an appropriate trial wave function, we reformulate the Gross-Pitaevskii equation with spherical symmetry as Newton's equation of motion for a particle in an effective potential, which is determined by the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 103 publications
0
23
0
Order By: Relevance
“…Collapsing boson condensates have been investigated by a number of groups [67,68,69,70,64,71,72,73]. Recently, we found that supercritical QCD axion condensates, having masses larger than the maximal allowed stable mass, collapse towards the global minimum of the effective axion potential [64,73].…”
Section: Discussionmentioning
confidence: 99%
“…Collapsing boson condensates have been investigated by a number of groups [67,68,69,70,64,71,72,73]. Recently, we found that supercritical QCD axion condensates, having masses larger than the maximal allowed stable mass, collapse towards the global minimum of the effective axion potential [64,73].…”
Section: Discussionmentioning
confidence: 99%
“…Time-dependent solutions to the GP equation can be approximated using the variational method formulation of Pethick and Smith [59], which we have described above. A good example of such an application is the collapse of BECs [26][27][28][29]. In this case, the variational parameter σ is taken to be a function of time, σ(t), while the wavefunction is multiplied by some phase.…”
Section: A General Formulationmentioning
confidence: 99%
“…Axion stars were considered first around 30 years ago, originally suggested to form from collapse of overdense miniclusters in the early universe [10,11] (see also more recent simulations [12]). Since then, many properties of axion stars have been studied extensively; these include structural stability [13][14][15][16][17][18][19][20][21][22] (including nonzero angular momentum [23][24][25]), the process of gravitational collapse [26][27][28][29][30][31][32], and their decay through emission of relativistic particles [33][34][35][36][37][38]. There has recently been a significant amount of work regarding relativistic corrections more generally to the classical field description of axion stars [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collapse of dark matter halos consisting of condensed scalar particles was examined by [37], using a time-dependent formalism that originated in [38], and utilized by [26,39]. The application of this method to an axion star, at leading-order in the self-interaction potential, was recently performed by [29].…”
Section: Jhep12(2016)066mentioning
confidence: 99%